Clinical characteristics and removal of broken burs retained in the lower jaw - Xin Xing; Chao Gong; Zhi-Yi Ye; Kun Lv; Zhi Li (BMC Oral Health)
Abstract Background A broken bur retained in the lower jaw is an uncommon complication that occurs during the extraction of the impacted mandibular third molar. The purpose of this retrospective study was to investigate the clinical characteristics of the broken burs and review our experience with the removal of the broken burs in these cases. Methods All patients, who suffered the broken bur remained in the lower jaw due to the extraction of the impacted mandibular third molar and presented to our hospital from July 2019 to July 2024, were included in this retrospective study. Demographic information of these cases was analyzed by descriptive statistics and the treatment methods were summarized. Results Based on the location of the broken burs, these cases can be classified into three types: (1) in the mandible; (2) between the lingual alveolar bone and periosteum; and (3) in the soft tissue of the mouth floor. In the cases of type 1, the removal of the broken burs was assisted by a tooth-supported digital guiding plate that precisely located the broken bur. The localization of the broken burs in types 2 and 3 was based on the preoperative radiographs, and the removal of the broken burs in the two types was mainly dependent on the surgeons’ experience. All the broken burs were successfully removed, and all patients displayed uneventful healing. Conclusions The broken burs remained in the lower jaw due to the extraction of the impacted mandibular third molar assumes many forms. The key point for the successful removal of the broken burs is to choose the corresponding methods based on the location of the broken burs.